A dynamic hysteresis model for customized glass transition in amorphous polymer towards multiple shape memory effects. (1st December 2022) - Liu, Jingyun; Gorbacheva, Galina; Lu, Haibao; Wang, Jiazhi; Fu, Yong-Qing
Abstract: Coexistence of multiple and discrete segments as well as their distinctive hysteresis relaxations enables amorphous shape memory polymers (SMPs) exhibiting complex disordered dynamics, which is critical for the glass transition behavior to determine the shape memory effect (SME), but remained largely unexplored. In this study, a dynamic hysteresis model is proposed to explore the working principle and collective dynamics in discrete segments of amorphous SMPs, towards a dynamic connection between complex relaxation hysteresis and glass transition behavior, which can be applied for design and realization of multiple SMEs in the amorphous SMPs. In combination of free volume theory and Adam-Gibbs domain size model, a phase transition model is formulated to identify the working principle of dynamic relaxation hysteresis in the glass transition of amorphous SMP. Furthermore, constitutive relationships among relaxation time, strain, storage modulus, loss angle and temperature have been established to describe the dynamic connection between complex relaxation hysteresis and customized glass transition, which is then utilized to achieve multiple SMEs based on the extended Maxwell model. Finally, effectiveness of the proposed models is verified using experimental results of SMPs with multiple SMEs reported in literature.